Empowerment of Housewives Group in Sabilambo Village through Training on Making Catfish Meatballs as an Effort to Increase Family Income - Essa Annisa Syadiah; Hasbiadi Hasbiadi; Fitrianti Handayani (Peneliti Teknologi Teknik Indonesia, 2021)
Kolaka Regency is one of the regencies in Southeast Sulawesi Province. The pond area in Kolaka marks it as one of the peculiarities of the region, moreover the majority of the heads of their families have jobs as pond farmers. Inland fishery business remains the main business field, because it is a sector that produces local community consumption as well as fishery product distribution channel business for processing industry companies. In Sabilambo Village, most of the women only work as housewives. In general, a housewife has enough free time to do activities that can increase her income. So far, the catch of this fish is only processed as ordinary kitchen preparations by the women of Sabilambo Village with stir-fried spices and yellow gravy. Meanwhile, the fish will have added value if it is used to be processed into diversified food products. Community empowerment service in Sabilambo Village aims to provide housewives with references to make additional income through training in making catfish meatballs. Improving the insight and capability of human resources is the main thing in economic development in a region.